Anakinra, a recombinant human IL-1 receptor antagonist, in clinical practice. Outcome in 60 patients with severe rheumatoid arthritis - S. Todesco; U. Fiocco; M. Biscaro; P. Ostuni; A. Furlan; P. Sfriso; C. Botsios; L. Punzi (PAGEPress Publications, 2011)
Objective: We evaluated both the efficacy and safety of anakinra in daily routine rheumatoid arthritis clinical practice. Methods:We studied 60 cases, including patients with previous anti-TNFα exposure, treated with anakinra (100 mg/daily s.c.) in combination with methotrexate (7.5-10 mg/week i.m.) or leflunomide (20 mg/die) in a two year observational study. Efficacy measures were assessed using the American College of Rheumatology (ACR) response criteria. Safety was evaluated according to a modified World Health Organization adverse reaction term dictionary. Results: At week 14, ACR 20% response criteria have been fulfilled by 53 (91.3%) out of 58 patients, 51 (87.9%) of them achieving also an ACR 50%and 15 (25.8%) an ACR 70%response. Thirteen patients touched 102 weeks of treatment: ACR 20% response was achieved in 92.3%, while ACR 50% and ACR 70% were respectively found in 84.6% and 38.4% of the cases. The mean decrease in HAQ score was 0.38, p<0.001. Of the 16 patients who were previously treated with anti-TNFα blockers, 81.2% responded to anakinra. There was no significant difference in the ACR response between groups with and without previous anti-TNFα exposure. Seventeen patients (28.3%) stopped anakinra because of side-effects (5%) or failure to respond (23.3%). Only 4 cases of pulmonitis, of which 2 have been hospitalised, and 1 case with tuberculosis (previously treated with infliximab) were observed. Conclusions: Our clinical experience confirms that anakinra is effective and safe in the treatment of rheumatoid arthritis. Anakinra seems also useful in patients with previous anti-TNFα blockers failures. Even though major adverse events were rare, clinicians should be aware of such a possibility